The comparative macroanatomfc researches oıı bones of yving (ossea alaej in rock partridges (a. graectı) and pheasants (p. colchicus) - Sefa Lök; Hakan Yalçın (Eurasian Journal of Veterinary Sciences)
The purpose of this study is to determine the macroanatomy of humerus, radius, ulna, ossa carpi, carpometacarpus and ossa digitorum manus forming bones ol wing in rock partridges and rigneck pheasant and to compare the differences between them. In this research, 10 rock partridges and 10 rigneck pheasant, ten weeks old, were used. Length measures and definite anatomic formations were determined. Humerus was in a pneumatic structure in both species. Partridges measures ol all bone length were always lower than pheasants measures. In all partridges, formations of impressio coracobrachialis and fossa penumotricipitalis at the level o) humerus proximal were observed as a deeper structure, in all pheasants, radius had more evident external curve than the the radius in partridges, but. in contrast, the inclination to outward of ulna was more definite in partridges. Os carpi radiale of the pheasants was a disordered guadrangle or like a bow-tie. In all pheasants and partridges, it was determined that 1. finger consists of one phalanx, 2. tinger consists of two phalanxes and 3. finger consists ol one phalanx. In conclusion, when partridges and pheasants bone ol wing are compared whit other bird species, evident differences wore determined. It was observed that there were some macroanatomic differences between partridges and pheasants.